Impact of organization member attributes on organizational resilience: The case of Banana Leaf Curry House Inc. - Alba, Vernice Freud Faustino (Animo Repository, 2023)
The study aims to find the effects of the three independent variables namely Organization Member Proficiency, Organization Member Adaptivity, and Organization Member Proactivity on the dependent variable, Organizational Resilience. The first independent variable, Organization Member Proficiency, refers to the organization that includes members who are proficient and competent in a specific set of skills that can help them achieve their goals (Dixon, 2015). In addition, the sub-variables for this variable are improvisation capability and learning capability from the study by Zhang & Merchant (2020). The next independent variable, Organization Member Adaptivity, refers to the ability of the employees inside the organization to overcome challenges brought by unexpected challenges (Savickas, 2013 as cited by Hirschi et al., 2015). The sub-variables for this variable are career development, work autonomy, and employee voice which comes from the study of Huntsman et al., (2021). The third independent variable namely Organization Member Proactivity refers to having a mentality of being proactive or initiating changes to benefit the organization and this also relates to the organization having the capacity to incite change within the organization (Bourmistrouv & Amo, 2022). The sub-variables for this variable are feedback seeking, job change negotiating, general socialization, and information seeking which comes from the study of Pennaforte(2016). As for the dependent variable Organizational Resilience, it refers to the organization's ability to recover after a disruptive occurrence (Hosseini et al., 2016). The sub-variables for this variable are resilience formalisation, location, external crisis events, prevention, strategic formalisation and networks which come from the study of Herbane (2019). The study utilizes both a quantitative and qualitative data gathering method. For the quantitative data, a survey on Google Forms was created and 60 employees from different departments, branches, and ages ranging iii from 18-49 years old were chosen as survey respondents. To organize and present the demographics of the respondents, different tools were used namely histogram, and frequency table. In addition, to further analyze the data, the group utilized different statistical methods such as the Durbin-Watson test, Normality test (Shapiro-Wilk), Linear regression, and multiple linear regression. As for the qualitative data, 4 managers from different positions were interviewed. In addition, to further understand the data and compare it to the quantitative data, a method called pattern matching was utilized. The results showed that Organization Member Adaptivity, and Organization Member Proactivity have a significant effect on Organizational Resilience while Organization Member Proficiency does not. Keywords: Organization Member Proficiency; Organization Member Adaptivity; Organization Member Proactivity; Organizational Resilience